Private and Public Sector Platforms - Characteristics and Differences - Lydia Ottlewski; Johanna Franziska Gollnhofer (Marketing Review St.Gallen, 2019)
Private sector platforms allow for new ways of doing business by connecting different market actors. Recently, public sector platforms have emerged that engage consumer citizens for economic and societal challenges. This paper conceptualizes such platforms, based on a thorough literature review and an empirical data collection. We provide five defining characteristics of platforms and show how private and public sector platforms differ.
Keywords: 650